Analysis of University Mobility and Internationalization in Institutional Accreditation Processes in Higher Education in Peru - Riojas Rivera, Jimmy Ronald; López Gonzales, Javier Linkolk (LACCEI, 2025)
This study examines the interconnections between university mobility, internationalization, and institutional accreditation processes in Peruvian higher education institutions. Using a quantitative, non-experimental cross-sectional design, data were collected from 68 licensed public and private universities through structured surveys administered to international relations and academic quality officials. Secondary data from Peru’s National System for the Evaluation, Accreditation, and Certification of Educational Quality (SINEACE) were incorporated to verify accreditation records. Statistical analyses included Shapiro-Wilk normality tests, ANOVA, and Spearman rank correlations using R Studio. Results revealed consistently positive perceptions of internationalization policies across institutions, with no significant differences between public and private universities in academic mobility (F(1,38) = 0.13, p = 0.721). However, weak correlations were found between mobility, policies, resources, and accreditation outcomes (ρ ≤ 0.20), indicating fragmented processes. Accreditation efforts were heavily concentrated at the undergraduate level (92.6%), with minimal representation in master’s (5.9%) and doctoral programs (1.5%). Disciplinary segmentation emerged, with public universities leading in engineering and health program accreditation, while private institutions focused on social sciences. The findings suggest that despite progress in establishing internationalization frameworks, operational gaps and lack of synergy persist. This research contributes to understanding higher education quality assurance in Latin America.